Interplay Between Reading Strategies and Comprehension Challenges in Academic Reading: Insights from Indonesian EFL Learners - Ferdinandus, Marcy Saartje; Simantuak, Jamaludin (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2024)
Reading academic texts in a second or foreign language involves substantial cognitive and linguistic demands, particularly for learners in English as a Foreign Language (EFL) contexts. Although various reading strategies, global, problem-solving, and support, have been widely theorized, their dynamic interaction with comprehension challenges remains underexplored, especially in Indonesian higher education. This study investigates the interplay between reading strategies and comprehension challenges among Indonesian EFL learners. Using a mixed-method design, 60 English Department students at Pattimura University were purposively selected. Quantitative data were collected through the Metacognitive Awareness of Reading Strategies Inventory (MARSI) and a researcher-developed Reading Comprehension Challenges Inventory, while qualitative data were obtained via semi-structured interviews with 10 participants. Quantitative results showed that global and problem-solving strategies were most frequently used, with their effectiveness varying by challenge type. Correlation and regression analyses revealed that global strategies aided conceptual connections, whereas problem-solving strategies addressed lexical and syntactic barriers. Thematic analysis showed that support strategies often failed with abstract concepts. These findings highlight an interactive, rather than linear, relationship between strategy use and comprehension challenges. The study contributes to applied linguistics by proposing a strategy–challenge interplay model and demonstrates the value of integrated methodological approaches for informing pedagogical practices in academic reading instruction.